PENINGKATAN KETERAMPILAN MENGEMUKAKAN PENDAPAT MATA PELAJARAN BAHASA INDONESIA MATERI MENGOMENTARI PERSOALAN FAKTUAL MENGGUNAKAN METODE TIME TOKEN SISWA KELAS V MI TARBIYATUL AKHLAQ TAMAN SIDOARJO - Ilmiyah, Siti Wasiatul (Journal Of Islamic Elementary School (JIES), 2017)
Skills in expressing opinions. The material for commenting on factual issues for fifth grade students of MI Arbiyatul Akhlaq Taman Sidoarjo is still low. This is reflected in the average value before the research was carried out below the KKM value. The purpose of this classroom action research is to find out the learning process before the Time Tiken method is applied to Indonesian subjects in class V MI Tarbiyatul Akhlaq and to find out the application of the Time Token method in improving the skills of expressing opinions for students in class V MI Tarbiyatul Akhlaq Krembangan, Taman and to find out improving the skills of expressing students' opinions using the time token method for class V MI Tarbiyatul Akhlaq, Krembangan, Taman. The research method used is a class action research model of Kurt Lewin. The action given is the time token method which is carried out in two cycles. Data collection techniques used are interviews, observation, documentation and performance tests. The instrument used is the teacher and student activity observation sheet and the performance test assessment rubric. The results of this study indicate that the skills of expressing students' opinions before the time token method was applied, there were 6 out of 20 students who achieved the completeness criteria value above the KKM. The application of the time token method in learning Indonesian is carried out effectively in improving the skills of expressing students' opinions. This is evidenced in the first cycle the student's observation value is 71%, in the second cycle it reaches 92%. While the value of teacher activity observations in the first cycle is 72%, the second cycle is 92%. 3) learning using the time token method can improve the skills of expressing students' opinions. From the results of data analysis, the students' classical mastery scores increased in the first cycle by 67% to 95% in the second cycle.